Sustitución parcial de harina de Trigo (Triticum Aestivum L) por mezcla de Quinua, Avena y Soya para la elaboración de galletas semiblanda con frutos secos. - Ruiz Serrano, María del Cisne (2015)
In the present work it has focused on degree partial substitution of wheat flour (Triticum aestivum L) of a mixture of quinoa, oats and soybeans with the addition of dried fruits such as raisins, walnuts and almonds to prepare a biscuit semi-soft type governed by parameters of NORMA INEN 2085: 2005. At work titling base a normal cookie formulation with 100% wheat was given, from there the partial substitution was performed by calculation of a mixture of quinoa, oats and soybeans, with the following percentages, for formulation A 70% wheat and 30% mixture, (quinoa, oats and soybeans) for formulation B 60% wheat and 40% mixture (quinoa, oats and soybeans).